VIABILIDADE DE IMPLANTAÇÃO DE USINA DE BIODIESEL UTILIZANDO ÓLEOS DE FRITURAS EM MUNICÍPIO DE GRANDE PORTE - Barbosa, Luis Adriano Ribeiro (2014)
It Is the growing environmental concern. Growing are also the concerns to develop means of achieving sustainability to minimize impacts to the planet as a result of the production chain. This study proposes an alternative to use of residual oil frying as a way to give another option to supply chain with regard to non-contamination of soils and aquifers. Thus were field trials designed to assess how much is wasted by official shops. Due this a review of the quantities produced and which could be reused effectively in biodiesel were raised in this paper. Market research focused on the choice of Biodiesel plant for processing this waste. Economic feasibility study for this plant was developed and confirmed its financial return. Arising from this, the first sector of the city studied, São Luis MA, has extensive work to be done in order to contribute to the processing of waste and become less and less environmental footprint of economic production cycle. A portion can be only a difference of minor importance, but the payment of all result in a planet with greater sustainability for all.